Constitutional Violations by the Health Care Quality Improvement Act (HCQIA) and the Reporting by the National Practitioner Databank (NPDB): Focusing on the Preservation of the Civil Rights of Physicians - Farid Gharagozloo, M.D.,FACHE; Robert Poston, M.D.; Rainer W.G. Gruessner, M.D. (British Journal of Healthcare and Medical Research, 2023)
In 1986, the US Congress passed the Health Care Quality Improvement Act of 1986. (HCQIA) was designed to protect the health and safety of the public by 1) enhancing the Peer Review process through protection for peer review members from lawsuits, and 2) providing a national repository for reported information regarding medical malpractice payments and adverse actions involving physicians, which among other things, would monitor the movement of incompetent or unprofessional physicians. The framers of HCQIA did not foresee that in 2023, hospitals and employers will invariably deny employment and/or hospital privileges based on an NPDB report outlining loss of hospital privileges or relinquishment of hospital privileges under investigation. Such an adverse report by NPDB results in the inability of the physician to obtain employment or practice in a hospital. Therefore, in 2023, the unintended consequence of the reporting of adverse peer review actions by NPDB, an agency of the Federal Government, can violate the constitutional and civil rights of the said physicians. The NPDB reporting provision of HCQIA violates 5th, 8th, 9th and 10th amendments of the Constitution.